Finding the Synoptic Gospels' Construction Process : A Comparative-Linguistic Analysis of the Eucharist and Its Co-texts - Ahn, Hojoon J., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
This study critically examines the current state of Synoptic Gospel studies, particularly many scholars' reliance on the Literary Dependence Hypothesis, and endeavors to advance a more balanced approach. The author attempts to deduce the Synoptic Gospels' construction process by meticulously examining the Eucharist and its co-text within these Gospels, by employing a model of Mode Register Analysis based on Systemic Functional Linguistics. This study uncovers the probability that each designated text in the Synoptic Gospels was constructed based on oral Gospel tradition(s) under the influence of each constructor's identity.